2024
DOI: 10.1101/2024.05.25.595842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zika virus infection in a cell culture model reflects the transcriptomic signatures in patients

Gillian Berglund,
Claudia D. Lennon,
Pheonah Badu
et al.

Abstract: Zika virus (ZIKV), a re-emerging flavivirus, is associated with devasting developmental and neurological disease outcomes particularly in infants infected in utero. Towards understanding the molecular underpinnings of the unique ZIKV disease pathologies, numerous transcriptome-wide studies have been undertaken. Notably, these studies have overlooked the assimilation of RNA-seq analysis from ZIKV-infected patients with cell culture model systems. In this study we find that ZIKV-infection of human lung adenocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…Together, these data indicated that peak viral protein and RNA expression coincided with ATF3 RNA and protein expression. Moreover, the induction of ATF3 expression during ZIKV infection is consistent with increased ATF3 levels in two biologically relevant systems to ZIKV infection namely SH-SY5Y neuronal cells and peripheral blood mononuclear cells (PBMCs) isolated from ZIKV-infected patients (39,40).…”
Section: Zikv Induces Strong Atf3 Expression 24-hours Post Infectionmentioning
confidence: 60%
See 3 more Smart Citations
“…Together, these data indicated that peak viral protein and RNA expression coincided with ATF3 RNA and protein expression. Moreover, the induction of ATF3 expression during ZIKV infection is consistent with increased ATF3 levels in two biologically relevant systems to ZIKV infection namely SH-SY5Y neuronal cells and peripheral blood mononuclear cells (PBMCs) isolated from ZIKV-infected patients (39,40).…”
Section: Zikv Induces Strong Atf3 Expression 24-hours Post Infectionmentioning
confidence: 60%
“…In a previous gene expression study, we observed that ZIKV PRVABC59 (ZIKV PR ) infection in a neuronal cell line (SH-SY5Y) stimulated immune and stress response genes such as ATF3 and CHOP (39). Moreover, in a reanalysis of RNA-seq data collected from peripheral blood mononuclear cells from patients in early- and late-acute and convalescent stages of ZIKV infection, we determined that ATF3 levels were increased (40). To determine when ATF3 was stimulated during ZIKV infection, we infected cells with ZIKV and examined viral and cellular proteins and RNA levels at different timepoints following infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations